Microstructural Changes in Clays Generated by Compression Explored by Means of SEM and Image Processing. (2016) - Cotecchia, Federica; Cafaro, Francesco; Guglielmi, Simona
Abstract: A study on the microstructure of an illitic marine clay is carried out through a thorough investigation of the clay origin, composition and current microstructure. The clay fabric is investigated by means of scanning electron microscopy (SEM) and statistically analysed by means of image processing. The nature and strength of the clay bonding are probed by means of direct chemical micro-analyses and on purpose strain paths. The same investigation is carried out both on the natural and on the reconstituted clay, at the initial state and after one-dimensional compression to medium and large pressures.